Correction: Analysis on the energetics, magnetism and electronic properties in a 45° ZnO grain boundary doped with Gd. Issue 5 (18th January 2019) - Sasikala Devi, Assa Aravindh; Roqan, Iman S.
Abstract : Correction for 'Analysis on the energetics, magnetism and electronic properties in a 45° ZnO grain boundary doped with Gd' by Assa Aravindh Sasikala Devi et al., RSC Adv., 2018, 8, 13850–13856.